APRESIASI KARYA SASTRA SEBAGAI MEDIA PENANAMAN MORALITAS DALAM DAKWAH - Ika Selviana (Ath Thariq Jurnal Dakwah dan Komunikasi, 2018)
Literary work is a subtle medium in conveying the values ​​of morality in da'wah. The beauty of words in literature can provide entertainment and imply the values ​​of personality that can teach goodness. So many moral values ​​that can be presented by literary works as a means of someone to convey the message of da'wah with beautiful sentences. So in addition to the works of literature can provide entertainment, the readers can also reap the wisdom of the message of da'wah presented the author with a beautiful and interesting language. The moral value can also be derived from the character of the story in the novel as well as from the beauty of the poetic sentence presented by a poet. The theme of love in literature such as the simple novel "Garis Waktu" from Fiersa Besari and the anthology of "Asal Muasal Pelukan" from Chandra Malik is an alternative to reading that is not only entertaining but implies moral values. although the main theme in this literary work is not including religious themes, but this work contains many good moral values ​​and can be applied in the behavior of community life. da'wah method through literary works is expected to be an alternative in the planting of morality without a sense of patronizing.